2021
DOI: 10.1155/2021/9523442
|View full text |Cite
|
Sign up to set email alerts
|

Independent Factors Affecting Postoperative Short-Term Urinary Continence Recovery after Robot-Assisted Radical Prostatectomy

Abstract: Background. Our team had firstly applied the transvesical approach to robot-assisted radical prostatectomy (RARP) in patients afflicted with localized prostate cancer (PCa). The present study aims to present the postoperative recovery of urinary continence (UC) following the anterior, transvesical, and posterior approaches to RARP for localized PCa and evaluate the independent predictors to early UC recovery after RARP. Methods. Patients harboring localized PCa and receiving anterior, transvesical, and posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…At present, the modified methods of RARP are also diversified, and the latest research is mainly focused on different approaches to retain Retzius [22][23][24][25][26] . The results suggest that RS-RARP (Retzius sparing) had better postoperative continence recovery than C-RARP (traditional), while sexual function recovery rates were www.nature.com/scientificreports/ not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the modified methods of RARP are also diversified, and the latest research is mainly focused on different approaches to retain Retzius [22][23][24][25][26] . The results suggest that RS-RARP (Retzius sparing) had better postoperative continence recovery than C-RARP (traditional), while sexual function recovery rates were www.nature.com/scientificreports/ not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 24 studies comparing RS-RARP to other approaches have been published up to April 15, 2023. Most reports aimed to demonstrate differences between RS-RARP and other approaches in terms of early and late urinary continence (Table 1) [5–8,9 ▪ ,10,11 ▪ ,12–16,17 ▪ ,18,19 ▪ ,20–22,23 ▪ ,24 ▪▪ ,25–28], but none focused on erectile function as primary endpoint. A minority of the studies reported data on sexual function, never finding significant differences among the RARP approaches.…”
Section: Literature Overviewmentioning
confidence: 99%